BUKU AUDIO SASTERA SEBAGAI ALTERNATIF PEMBACAAN KARYA SASTERA DALAM ERA DIGITAL: LITERARY AUDIOBOOKS AS ALTERNATIVE READING MATERIAL IN THE DIGITAL ERA - @ Mustafa, Madiawati Mamat; Tengku Mohd. Ali, Tengku Intan Marlina; Hashim, Nurhamizah; Hazari, Nur Asyirah (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract Audiobooks are one of the many mediums for the delivery of literary works in the digital age. However, audiobooks have existed since 1931. For example, the American Foundation for the Blind and the Library of Congress would provide audiobook-based programmes for the visually impaired. The use of this particular medium in Malay literature is still not considered widespread. After that, audiobooks started to flourish in the field of early childhood education and currently, there is a publishing company that produces audiobooks in Malaysia. However, its existence and evolution in literature are not widely known than to literary works delivered through other new media. This study, funded by the faculty grant GPF006K-2018, examined the various forms of literary audiobooks published by the company Nusantara as a means to provide alternative reading material in Malaysia. This study aimed to identify and discuss the history and development of literary audiobooks in Malaysia to highlight their form and importance in the digital era. This study utilised text analysis to examine past research on audiobooks and analysed various literary audiobooks available in the market. Additionally, interviews were conducted with different publishers to get their feedback regarding the general acceptance of such material amongst their customers. Findings showed that Nusantara Audiobooks actively publishes literary audiobooks, be it from Malaysia or Indonesia. In conclusion, these digital materials in the market would diversify reading methods and analyse literary works. Keywords: audiobooks, Malay literature, digital, alternative, evolution